A child with a novel ACAN missense variant mimicking a septic arthritis - Angelo Florio; Riccardo Papa; Roberta Caorsi; Alessandro Consolaro; Roberto Gastaldi; Marco Gattorno; Paolo Picco (BMC, 2019)
Abstract Heterozygous mutations of the ACAN gene have been associated with a broad spectrum of non-lethal skeletal dysplasias, called Aggrecanopathies. We report a case of a child with severe inflammatory elbow involvement mimicking septic arthritis who carried the new ACAN missense variant c.6970 T > C, p.Trp2324Arg. The comprehensive clinical evaluation of the patient and his family, focused on the associated clinical features (facial dysmorphisms, short stature, brachydactily), led us to suspect a hereditary condition. Our findings suggest that Aggrecanopathies should be considered in children with familial short stature, poor growth spurt and joint involvement.